The Effect of Samsung Electronics' Expansion to India on the South Korean Economy in 2017-2021 - Belina Averin Sebastian; Ganjar Widhiyoga; Untari Narulita Madyar Dewi (Insignia: Journal of International Relations, 2022)
Samsung is the largest multinational company in South Korea that has successfully expanded to various countries. India is the second largest technology market after China which is a new market in the Asian continent. Currently, India is being targeted by many world technology companies to market their products in the South Asian region, so this is an opportunity for Samsung to enter and expand in India. Samsung, which has successfully entered India, is always innovating in creating and developing pre-owned technology products to increase sales of its products. This also affects the South Korean economy, where with the expansion carried out by Samsung, the South Korean economy has experienced significant growth in terms of the increase in GDP every year which is the focus of this research. This study uses quantitative methods with descriptive statistical analysis methods by providing additional data in the form of graphs. Samsung's successful expansion to India is marked by investments in the construction of new manufacturing plants in the Noida area, Uttar-Pradesh, and sales of Samsung products in India are the second largest with average avenue is 700 billion INR. These results also affect the economic position of South Korea so that it becomes a country that has a fairly strong position in the field of technological development. The conclusion of this study is that Samsung brought South Korea to be part of the category of developed countries in the world with significant GDP growth every year from the period 2017-2021.